You Get Adjusted. Though the Tension Prevailed - Klumbys, Valdemaras (Problemos, 2018)
[text in Lithuanian]Ipolitas Ledas interviewed by Valdemaras Klumbys. Vilnius, October 1, 2002.Editing and Commentaries by Valdemaras Klumbys.Document: audiorecord (160 min.), privat collection of V. Klumbys.
Keywords: none